SARS-CoV-2 seroprevalence among blood donors in Uganda: 2019–2022 - Bloch, Evan M; Kyeyune, Dorothy; White, Jodie L; Ddungu, Henry; Ashokkumar, Swetha; Habtehyimer, Feben; Baker, Owen; Kasirye, Ronnie; Patel, Eshan U.; Grabowski, M. Kate; Musisi, Ezra; Moses, Khan; et al. (John Wiley & Sons, Ltd, 2023)
Abstract Abstract Background The true burden of COVID‐19 in low‐ and middle‐income countries remains poorly characterized, especially in Africa. Even prior to the availability of SARS‐CoV‐2 vaccines, countries in Africa had lower numbers of reported COVID‐19 related hospitalizations and deaths than other regions globally. Methods Ugandan blood donors were evaluated between October 2019 and April 2022 for IgG antibodies to SARS‐CoV‐2 nucleocapsid (N), spike (S), and five variants of the S protein using multiplexed electrochemiluminescence immunoassays (MesoScale Diagnostics, Rockville, MD). Seropositivity for N and S was assigned using manufacturer‐provided cutoffs and trends in seroprevalence were estimated by quarter. Statistically significant associations between N and S antibody seropositivity and donor characteristics in November–December 2021 were assessed by chi‐square tests. Results A total of 5393 blood unit samples from donors were evaluated. N and S seropositivity increased throughout the pandemic to 82.6% in January–April 2022. Among seropositive individuals, N and S antibody levels increased ≥9‐fold over the study period. In November–December 2021, seropositivity to N and S antibody was higher among repeat donors (61.3%) compared with new donors (55.1%; p = .043) and among donors from Kampala (capital city of Uganda) compared with rural regions ( p = .007). Seropositivity to S antibody was significantly lower among HIV‐seropositive individuals (58.8% vs. 84.9%; p = .009). Conclusions Despite previously reported low numbers of COVID‐19 cases and related deaths in Uganda, high SARS‐CoV‐2 seroprevalence and increasing antibody levels among blood donors indicated that the country experienced high levels of infection over the course of the pandemic.
Keywords: Blood donors, COVID-19, epidemiology, SARS-CoV-2, serological testing, Uganda